Multitrait engineering of Hassawi red rice for sustainable cultivation - Sedeek, Khalid; Mohammed, Nahed; Zhou, Yong; Zuccolo, Andrea; Sanikommu, Krishnaveni; Kantharajappa, Sunitha; Al-Bader, Noor; Tashkandi, Manal; Wing, Rod A.; Mahfouz, Magdy M. (Elsevier, 2024)
Sustainable agriculture requires locally adapted varieties that produce nutritious food with limited agricultural inputs. Genome engineering represents a viable approach to develop cultivars that fulfill these criteria. For example, the red Hassawi rice, a native landrace of Saudi Arabia, tolerates local drought and high-salinity conditions and produces grain with diverse health-promoting phytochemicals. However, Hassawi has a long growth cycle, high cultivation costs, low productivity, and susceptibility to lodging. Here, to improve these undesirable traits via genome editing, we established efficient regeneration and Agrobacterium-mediated transformation protocols for Hassawi. In addition, we generated the first high-quality reference genome and targeted the key flowering repressor gene, Hd4, thus shortening the plant's lifecycle and height. Using CRISPR/Cas9 multiplexing, we simultaneously disrupted negative regulators of flowering time (Hd2, Hd4, and Hd5), grain size (GS3), grain number (GN1a), and plant height (Sd1). The resulting homozygous mutant lines flowered extremely early (∼56 days) and had shorter stems (approximately 107 cm), longer grains (by 5.1%), and more grains per plant (by 50.2%), thereby enhancing overall productivity. Furthermore, the awns of grains were 86.4% shorter compared to unedited plants. Moreover, the modified rice grain displayed improved nutritional attributes. As a result, the modified Hassawi rice combines several desirable traits that can incentivize large-scale cultivation and reduce malnutrition.